Evaluation of the methane full-physics retrieval applied to TROPOMI ocean sun glint measurements - Lorente, Alba; Borsdorff, Tobias; Martinez-Velarte, Mari C.; Butz, André; Hasekamp, Otto P.; Wu, Lianghai; Landgraf, Jochen (Atmospheric measurement techniques, 2022)
Abstract. The TROPOspheric Monitoring Instrument (TROPOMI), due to its wide swath, performs observations over the ocean in every orbit, enhancing the monitoring capabilities of methane from space. In the short-wave-infrared (SWIR) spectral band ocean surfaces are dark except for the specific sun glint geometry, for which the specular reflectance detected by the satellite provides a signal that is high enough to retrieve methane with high accuracy and precision. In this study, we build upon the RemoTeC full-physics retrieval algorithm for land measurements, and we retrieve 4 years of methane concentrations over the ocean from TROPOMI. We fully assess the quality of the dataset by performing a validation using ground-based measurements of the Total Carbon Column Observing Network (TCCON) from near-ocean sites. The validation results in an agreement of -0.5±0.3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="ffed11dcee09790e59a09f5b1ad09d26"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-15-6585-2022-ie00001.svg" width="52pt" height="10pt" src="amt-15-6585-2022-ie00001.png"/></svg:svg> % (-8.4±6.3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="507d7214a0ce03b208f842ea50c7da16"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-15-6585-2022-ie00002.svg" width="52pt" height="10pt" src="amt-15-6585-2022-ie00002.png"/></svg:svg> ppb) for the mean bias and station-to-station variability, which show that glint measurements comply with the mission requirement of precision and accuracy below 1 %. Comparison to ocean measurements from the Greenhouse gases Observing SATellite (GOSAT) results in a bias of -0.2±0.9<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="0ea40aa3db336ffa62152b497264004f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-15-6585-2022-ie00003.svg" width="52pt" height="10pt" src="amt-15-6585-2022-ie00003.png"/></svg:svg> % (-4.4±15.7<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="d5ddfa1e55423ce1115b1e279c3ea8ca"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-15-6585-2022-ie00004.svg" width="58pt" height="10pt" src="amt-15-6585-2022-ie00004.png"/></svg:svg> ppb), equivalent to the comparison of measurements over land. The full-physics algorithm simultaneously retrieves the amount of atmospheric methane and the physical scattering properties of the atmosphere from measurements in the near-infrared (NIR) and SWIR spectral bands. Based on the scattering properties of the atmosphere and ocean surface reflection we further validate retrievals over the ocean. Using the “upper-edge” method, we identify a set of ocean glint observations where scattering by aerosols and clouds can be ignored in the measurement simulation to investigate other possible error sources such as instrumental errors, radiometric inaccuracies or uncertainties related to spectroscopic absorption cross-sections. With this ensemble we evaluate the RemoTeC forward model via the validation of the total atmospheric oxygen (O2) column retrieved from the O2 A-band, as well as the consistency of XCH4 retrievals using sub-bands from the SWIR band, which show a consistency within 1 %. We discard any instrumental and radiometric errors by a calibration of the O2 absorption line strengths as suggested in the literature.
Gesehen am 21.12.2022